A Decadal Climate Cycle in the North Atlantic Ocean as Simulated by the ECHO Coupled GCM - Grötzner, A.; Latif, Mojib; Barnett, T. P. (AMS (American Meteorological Society), 1998)
In this paper a decadal climate cycle in the North Atlantic that was derived from an extended-range integration with a coupled ocean–atmosphere general circulation model is described. The decadal mode shares many features with the observed decadal variability in the North Atlantic. The period of the simulated oscillation, however, is somewhat longer than that estimated from observations. While the observations indicate a period of about 12 yr, the coupled model simulation yields a period of about 17 yr. The cyclic nature of the decadal variability implies some inherent predictability at these timescales. The decadal mode is based on unstable air–sea interactions and must be therefore regarded as an inherently coupled mode. It involves the subtropical gyre and the North Atlantic oscillation. The memory of the coupled system, however, resides in the ocean and is related to horizontal advection and to the oceanic adjustment to low-frequency wind stress curl variations. In particular, it is found that variations in the intensity of the Gulf Stream and its extension are crucial to the oscillation. Although differing in details, the North Atlantic decadal mode and the North Pacific mode described by M. Latif and T. P. Barnett are based on the same fundamental mechanism: a feedback loop between the wind driven subtropical gyre and the extratropical atmospheric circulation.